2020
DOI: 10.1371/journal.pone.0236723
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, associated factors, and comorbidities of tinnitus in adolescents

Abstract: The aim of this study was to investigate the prevalence of tinnitus among adolescents, and the factors known or hypothesized to be associated with tinnitus. Based on random sampling of school types and regions, a nationwide hearing survey of the first-year middle and high school students of South Korea was performed. The subjects underwent an otologic examination followed by pure tone audiometry up to 8 kHz. Questionnaires about the factors associated with hearing and tinnitus were completed by the students an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
1
18
0
3
Order By: Relevance
“…Consequently, a revised grading system is necessary for subjects of different genders groups and according to the hearing status based on the results of that study. Another investigation observed that tinnitus complaint was correlated with age, a contraindicated finding in our study population but was prominent in females according to our findings [ Rhee et al., 2020 ]. Oosterloo et al.…”
Section: Discussionsupporting
confidence: 57%
“…Consequently, a revised grading system is necessary for subjects of different genders groups and according to the hearing status based on the results of that study. Another investigation observed that tinnitus complaint was correlated with age, a contraindicated finding in our study population but was prominent in females according to our findings [ Rhee et al., 2020 ]. Oosterloo et al.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, the presence of temporary and chronic tinnitus in university students was higher as compared to adolescents in Flanders [41,42]. In addition to age, female gender, socio-economic status, attitudes, and noise exposure can be related to the occurrence of noise-induced tinnitus [20,27,28,40,43]. In the current study, another factor, educational program, influenced the presence of tinnitus.…”
Section: Discussionmentioning
confidence: 48%
“…For many people affected, tinnitus constitutes a massive burden with many potential psychological and physiological comorbidities [ 1 , 69 , 70 ], ultimately resulting in lower quality of life [ 71 , 72 ]. The used interventions in the UNITI-RCT might have the potential for brief or even prolonged tinnitus suppression as well as to help people to better cope respectively live with their tinnitus.…”
Section: Discussionmentioning
confidence: 99%